The Indian Society for Study of Pain, Cancer Pain Special Interest Group (SIG) guidelines, for the diagnosis and assessment of cancer pain - Aparna Chatterjee; Raghu S Thota; Raghavendra Ramanjulu; Arif Ahmed; Dipasri Bhattacharya; Naveen Salins; Parmanand Jain; Sushma Bhatnagar (Indian Journal of Pain, 2019)
The Indian Society for Study of Pain (ISSP), Cancer Pain Special Interest Group guidelines, for the diagnosis and assessment of cancer pain in adults provide a structured, step-wise approach which will help to improve the management of cancer pain and to provide the patients with a minimally acceptable quality of life. The guidelines have been developed based on the available literature and evidence, to suit the needs of patient population and situations in India. A questionnaire based on the key elements of each sub draft addressing certain inconclusive areas where evidence was lacking, was made available on the ISSP website and circulated by E-mail to all the ISSP and Indian Association of Palliative Care members. We recommend that a comprehensive pain assessment of all the patients should be conducted before initiating treatment. The patients should be educated about all the available pain control interventions. For assessing cancer pain, unidimensional tools such as Numeric Rating Scale, Visual Analog Scale, and Visual Rating Scale should always be used routinely. Patients with cancer pain should routinely be screened for distress and other psychological disorders, using the Patient Health Questionnaire-9. The most reliable assessment of pain is patients' self-reporting.